A Qualitative Study of the Experiences of Parents With an Adult Child Who Has a Severe Disease: Existential Questions Will Be Raised - Inger Benkel MSW, PhD; Ulla Molander MD, PhD (SAGE Publishing, 2017)
A prominent existential concept is that elderly parents should naturally become severely ill or die before a younger person does. If the reverse should happen, it may influence the parent's existential view of life. The aim of this study was to investigate the existential issues during illness time. This was a qualitative study with in-depth interviews and was conducted in a University Hospital in western Sweden. Eleven parents agreed to participate in individual interviews at baseline and 1 year later. The total number of interviews completed was 19. The study identified 5 areas according to an existential perspective: life took the wrong path, the age of the child, difficult to see the child as sick, worrying about the child , and the relationship with the adult child . Existential questions are often present in those circumstances and can be raised in conversations with parents. Existential questions began to arise for the parent when the child was diagnosed with the severe illness. The situation of having a severely ill child caused both fear and anxiety that the worst-case scenario they could imagine, that the child will die, might happen. Further research is required on this rarely investigated subject of having an adult child with a severe disease.